1996
DOI: 10.1002/pssa.2211540221
|View full text |Cite
|
Sign up to set email alerts
|

The Conduction Mechanism of Lithium—Germanium Ferrites

Abstract: The dc conductivity of the spinel structure compositions Lio.~+o.~xGexFe~.5~1.5x04, where x = 0, 0.2, 0.3, 0.5, is studied. This study shows the existence of two transition points. The first one is due to the Curie temperature TC which is 795, 508, 480, and 448 K for x = 0, 0.2, 0.3, and 0.5, respectively. The second point is related to the order-disorder transition TD which is 1012, 615, 595 K for x = 0, 0.2, 0.3, respectively. The latter point T, disappears for x = 0.5. The conduction mechanism is discussed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…[19]. The modification in electric and magnetic properties of A 3+ -ferrites, by substitution of different ions, has been studied by many investigators, [17,21,19,26,25,22,1,2]. In the present investigation a systematic study of the complex dielectric constant and loss tangent tan of Yttrium -Al-Ni ferrites has been carried out and the results are given in this paper.…”
Section: Introductionmentioning
confidence: 90%
“…[19]. The modification in electric and magnetic properties of A 3+ -ferrites, by substitution of different ions, has been studied by many investigators, [17,21,19,26,25,22,1,2]. In the present investigation a systematic study of the complex dielectric constant and loss tangent tan of Yttrium -Al-Ni ferrites has been carried out and the results are given in this paper.…”
Section: Introductionmentioning
confidence: 90%
“…Equation (6) gives an explanation to the decrease of the dielectric constant with the frequency. From the other hand, the behavior of dielectric constant with the frequency can be explained on the fact that the hopping of the charge carriers can not follow the frequency of the external applied electric field beyond a certain frequency value [19].…”
Section: By Inspection Ofmentioning
confidence: 99%
“…The crystal structure, microstructure and cation distribution have a remarkable effect on the ferrite properties and its applied aspects [2][3][4]. Several studies [1,[5][6][7][8] have been reported on the effect of additions of divalent, trivalent and tetravalent ions on the electrical conductivity and dielectric properties of lithium ferrites. In this work the conduction mechanism and the dielectric properties of Zn 1-x Li 0.5x Fe 2+0.5x O 4 , where x = 0.25, 0.5, 0.75 was undertaken…”
Section: Introductionmentioning
confidence: 99%
“…Several such types of studies have been reported for lithiated transition metal oxides [14][15][16][17][18][19][20][21][22][23]. This was motivated to prepare a LiCo 3/5 Fe 1/5 Cu 1/5 VO 4 compound and characterize its electrical impedance and modulus properties.…”
Section: Introductionmentioning
confidence: 98%